Pengaruh Komunikasi Interpersonal dan Kualitas Pelayanan Terhadap Kepuasan Konsumen - Enggarayu Weningtyas; Miftahun Ni'mah Suseno (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2012)
The General purpose of study was to determine the presence or absence of the influence of interpersonal communication and service quality toward consumer satisfaction. The hypothesis of this study is that there is the influence of interpersonal communication and service quality toward consumer satisfaction. The subject of this study were consumers who had visited Kalimilk. The subject of this study consisted of men and women aged 18-23 years, totaling 60 people at try out and 60 people at the time of the study data collection. Data collected through the scale is was propagated to the subject of research. The data is was then statistically analyzed using multiple regression analysis with SPSS version 16.0 for Windows. The analysis found that the value R = 0.777 with p = 0.000 (p <0.01). The magnitude of the coefficient of determination (R-Square) interpersonal communication and service quality to consumer satisfaction at 60.3% (0.603). The general conclusion of this study is was there is was a very significant positive effect between interpersonal communication and service quality toward consumer satisfaction. The higher the interpersonal communication skills and services quality provided employees the higher the consumer satisfaction.Keywords: Interpersonal Communication, Service Quality, Consumer